Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera: Ensifera: Stenopelmatoidea) XXVI: New additions based on the specimens from Southern China - Luo, Ting; Zhang, Hui; Bian, Xun (Zootaxa, 2024)
In this paper, we describe four new species based on the specimens from southern China: Glolarnaca flata sp. nov., Larnaca (Larnaca) nigrimargis sp. nov., Phryganogryllacris guangxiensis sp. nov. and Tenuigryllacris hainanensis sp. nov. In addition, the female sexes of four known species are described for the first time, namely: Apterolarnaca nigrifrontis Bian & Shi, 2016, Apterolarnaca quadrimaculata Bian & Shi, 2016, Dracogryllacris zhoui (Pang, Zhang & Bian, 2023) and Glolarnaca nigrimacula Yang, Lu & Bian, 2021. Also, two new synonyms (Apterolarnaca truncatoloba (Li & Liu, 2015) = Apterolarnaca spiculoproceris Zhang, Lu & Bian, 2022 syn. nov. and Marthogryllacris erythrocephala maculatis (Liu, Lu & Bian, 2022) = Marthogryllacris jinpingensis (Zhang & Bian, 2023) syn. nov.) are proposed based on molecular data. All the specimens are deposited in Guangxi Normal University.